2012
DOI: 10.1016/j.healthpol.2012.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive care programs for patients with multiple chronic conditions: A systematic literature review

Abstract: Because of the heterogeneity of comprehensive care programs, it is as yet too early to draw firm conclusions regarding their effectiveness. More rigorous evaluation studies are necessary to determine what constitutes best care for the increasing number of people with multiple chronic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
182
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(189 citation statements)
references
References 85 publications
(300 reference statements)
3
182
0
4
Order By: Relevance
“…Furthermore, an increasing number of people in Europe (about 50 million) are suffering from multiple chronic conditions or multimorbidity [2,3], of which 60% are people aged 65 years and older [4]. This leads to poor quality of life and high healthcare utilization, reflected in for example elevated numbers of primary care consultations and (ICTs) that could potentially improve self-management, information systems, remote monitoring and independent living solutions [11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an increasing number of people in Europe (about 50 million) are suffering from multiple chronic conditions or multimorbidity [2,3], of which 60% are people aged 65 years and older [4]. This leads to poor quality of life and high healthcare utilization, reflected in for example elevated numbers of primary care consultations and (ICTs) that could potentially improve self-management, information systems, remote monitoring and independent living solutions [11].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there will be growing numbers of older people who cope with multiple and/or chronic health conditions (De Bruin et al, 2012;World Health Organization, 2009) who likely require more extensive forms of health care (Eklund & Wilhelmson, 2009). To face up to this development governments of ageing populations need to adapt their health and care policies.…”
Section: Introductionmentioning
confidence: 99%
“…5 Chronic illness management (CIM), a care model which emphasizes continuity of care and promotes self-management support for patients, could therefore provide an opportunity to improve long-term outcomes post HTx given promising results in other chronic patient populations. 5,8,9 Studies in non-HTx populations have shown that CIM is associated with decreased healthcare utilization, 10,11 improvements in health-related behaviors, 12 increased quality-of-life, 11 and greater patient and caregiver satisfaction. 12 In transplantation, the reengineering of transplant follow-up care according to the principles of CIM has resulted in improved clinical outcomes, reduced health care utilization, and reduced costs.…”
Section: Introductionmentioning
confidence: 99%
“…5,8,9 Studies in non-HTx populations have shown that CIM is associated with decreased healthcare utilization, 10,11 improvements in health-related behaviors, 12 increased quality-of-life, 11 and greater patient and caregiver satisfaction. 12 In transplantation, the reengineering of transplant follow-up care according to the principles of CIM has resulted in improved clinical outcomes, reduced health care utilization, and reduced costs. 10,13 In the most recent guidelines for the care of HTx recipients, the International Society of Heart and Lung Transplantation (ISHLT) recommended that transplant centers utilize a multidisciplinary approach to patient management.…”
Section: Introductionmentioning
confidence: 99%